An ordered face-centered cubic Fe-Ga thermoelectric material and a preparation method and application thereof

CN122959607APending Publication Date: 2026-10-23INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611376523.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,纯有序面心立方相的制备面临严格的热力学与动力学限制:Ga含量需精确控制在26-29 at%范围内,退火温度400-550℃,且降温速率须小于8 K·min-1;快速冷却会严重抑制有序面心立方相的形核,极易形成有序立方D03相与有序面心立方L12相的混合相,难以获得纯相材料

Benefits of technology

[0028]与现有技术相比,本发明可实现以下有益效果中的一项或多项:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959607A_ABST
    Figure CN122959607A_ABST
Patent Text Reader

Abstract

This invention provides an ordered face-centered cubic Fe-Ga thermoelectric material, its preparation method, and its applications. The preparation method includes: according to the chemical formula Fe... x Ga 4‑x The raw materials were batched and smelted to obtain alloy ingots, wherein 2.85 ≤ x ≤ 3.05; DO3 phase alloy strips were produced by single-roll melt spinning; and then spun under vacuum at ≤ 8 K·min ‑1 The heating and cooling rates were controlled, and annealing was performed at 450-550℃ to transform the DO3 phase into a pure L12 phase, thus obtaining an ordered face-centered cubic Fe-Ga thermoelectric material. This invention represents the first successful controllable preparation of a pure L12 phase Fe-Ga alloy and polarity reversal through a room-temperature anomalous Nernst effect, wherein the L12 phase Fe... 2.95 Ga 1.05 The anomalous Nernst coefficient at room temperature reaches 8.5 μV·K. ‑ ¹, the efficiency is nearly twice that of the DO3 phase with the same composition. The material of this invention has the advantages of high performance, adjustable polarity, and controllable process, and has important application prospects in fields such as lateral thermoelectric power generation, waste heat recovery, flexible sensing, and micro energy harvesting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermoelectric materials technology, specifically to a Fe-Ga alloy thermoelectric material with an ordered face-centered cubic crystal structure, its preparation method, and its application in thermoelectric energy conversion devices. Background Technology

[0002] With the increasing prominence of energy and environmental issues, the recovery and utilization of low-grade heat energy, such as industrial waste heat, waste heat from electronic devices, and body temperature differences in wearable devices, has received widespread attention. Thermoelectric conversion technology can directly convert heat energy into electrical energy, offering advantages such as no moving mechanical parts, maintenance-free operation, and easy modularization, making it particularly suitable for utilizing low-grade heat energy in harsh environments. Traditional thermoelectric technology mainly relies on the Seebeck effect (longitudinal thermoelectric effect), where the direction of electrical transport is parallel to the direction of heat transport, resulting in strong coupling between phonon and electron transport, making independent control difficult. Furthermore, it requires the pairing and integration of P-type and N-type semiconductors, and the bipolar effect at high temperatures causes a significant decrease in the Seebeck coefficient. In addition, the thermoelectric figure of merit ZT is constrained by the Wiedemann-Frantz law (WF law), and its peak value is usually difficult to exceed 2, encountering a bottleneck in improving conversion efficiency.

[0003] The anomalous Nernst effect (ANE), a transverse thermoelectric effect, can directly convert the temperature gradient in a magnetic material into a transverse voltage under zero magnetic field conditions, thus overcoming the limitations of traditional Seebeck devices. Because the electrical and thermal transport directions are perpendicular, electroacoustic decoupling is achieved and the bipolar effect is eliminated; the device requires only a single magnetic material, eliminating the need for PN junction pairs, greatly simplifying the structure; its thermoelectric quality factor ZT NE It is not limited by the traditional WF law and has a higher potential for conversion efficiency.

[0004] Magnetic topological materials, due to the large Berry curvature near the Fermi surface, can generate anomalous Nernst effect with topological enhancement, making them a research focus in this field. Among them, iron-based binary Fe-Ga alloys have advantages such as low raw material cost, high abundance in the Earth's crust, good chemical stability, and strong compatibility with thin film growth, and are considered to be a lateral thermoelectric material system with great industrialization potential.

[0005] Existing research indicates that the anomalous Nernst coefficient of D03 phase Fe3Ga bulk material can reach 5.8 μV·K at room temperature. -1It is comparable to the classic Weyl half-metal Co₂MnGa. However, the D₀₃ phase is a complex cubic ordered structure with a space group of Fm-3m, and its structural stability and thermoelectric transport properties have many limitations. This D₀₃ phase system faces several insurmountable technical obstacles: First, the D₀₃ phase is metastable at room temperature and is prone to phase transition at high temperatures, resulting in severely insufficient performance stability; second, improving the anomalous Nernst coefficient by simply fine-tuning the Fermi level through composition usually results in an improvement of less than 10%, which is far from meeting the requirements for practical application; third, this material only exhibits a unipolar anomalous Nernst effect, requiring the alternating splicing of different materials when fabricating thermopile devices, significantly increasing integration complexity and manufacturing costs.

[0006] Fe-Ga alloys exhibit various crystal structures, including disordered A2 phase, ordered D03 and B2 phases, and an ordered face-centered cubic (FCC) L12 phase. The D03 phase is metastable at room temperature, while the ordered FCC L12 phase is stable at room temperature. Theoretically, it is predicted to exhibit a large anomalous Nernst effect and can be obtained from the D03 phase through heat treatment. However, the preparation of the pure ordered FCC phase faces strict thermodynamic and kinetic limitations: the Ga content must be precisely controlled within the range of 26-29 at%, the annealing temperature must be 400-550℃, and the cooling rate must be less than 8 K·min. -1 Rapid cooling severely inhibits the nucleation of the ordered face-centered cubic phase, making it easy to form a mixed phase of ordered cubic D03 and ordered face-centered cubic L12 phases, thus making it difficult to obtain pure phase materials.

[0007] Therefore, how to achieve the controllable preparation of Fe-Ga alloys with pure ordered face-centered cubic structure, and realize room-temperature bipolar transport while significantly improving the anomalous Nernst effect, has become a key requirement for breaking through the bottleneck of transverse thermoelectric technology and promoting its practical application. Summary of the Invention

[0008] The purpose of this invention is to provide a Fe-Ga thermoelectric material with an ordered face-centered cubic structure and its preparation method. By using a vacuum annealing process, a controllable phase transition from the metastable DO3 phase to the stable ordered face-centered cubic phase of the Fe-Ga alloy is achieved, resulting in a novel iron-based magnetic topological thermoelectric material. At the same time, by precisely controlling the stoichiometric ratio of Fe to Ga, the anomalous Nernst coefficient of the ordered face-centered cubic phase alloy at room temperature is maximized, and the polarity reversal of the anomalous Nernst effect at room temperature is achieved for the first time.

[0009] Through in-depth research, the inventors discovered that first, Fe... x Ga 4-xThe alloy was prepared into DO3 phase alloy strips through arc melting and single-roll melt spinning, and then treated with a specific vacuum annealing process to achieve a complete phase transformation from the DO3 phase to the ordered face-centered cubic L12 phase. However, pure L12 phase can only be obtained within a narrow composition range of 2.85 ≤ x ≤ 3.05. Within this range, fine-tuning the molar ratio of Fe can not only control the amplitude of the anomalous Nernst effect but also reverse its polarity. The unique structure of the L12 phase results in significantly better anomalous Nernst coefficient, anomalous Hall resistivity, and transverse thermal conductivity than the traditional DO3 phase Fe-Ga. This is the first time that the controllable preparation of pure L12 phase and the polarity control of the room-temperature anomalous Nernst effect have been achieved in an iron-based binary alloy system. The prepared material has extremely high application value in the fields of transverse thermoelectric conversion, waste heat recovery, and micro thermoelectric devices.

[0010] To achieve the aforementioned objective, the present invention provides the following technical solution.

[0011] In a first aspect, the present invention provides a method for preparing an ordered face-centered cubic Fe-Ga thermoelectric material, comprising the following steps:

[0012] (1) According to the chemical formula Fe x Ga 4-x The ingredients are batched and smelted to obtain an alloy ingot, where 2.85 ≤ x ≤ 3.05;

[0013] (2) The alloy ingot is processed into DO3 phase alloy strips by single-roll melt spinning;

[0014] (3) The D03 phase alloy strip is annealed under vacuum conditions, the annealing process including: first at ≤8 K·min -1 Heat to an annealing temperature of 450-550℃ at a heating rate, hold at that temperature, and then heat at ≤8 K·min. -1 The temperature is cooled to room temperature at a decreasing rate, causing the D03 phase to transform into the pure L12 phase, thus obtaining the ordered face-centered cubic Fe-Ga thermoelectric material.

[0015] Through in-depth research, the inventors of this invention have discovered for the first time that in order to achieve the controllable preparation of pure ordered face-centered cubic (i.e., pure L12 phase) Fe-Ga alloys, two conditions must be met simultaneously: first, the molar ratio of Fe, x, must be controlled within a narrow range of 2.85 to 3.05; second, the precursor D03 phase alloy strips must undergo a solid-state phase transformation under a specific annealing process.

[0016] In step (1), the stoichiometric ratio is limited to 2.85 ≤ x ≤ 3.05 because: when x is below 2.85, the Ga content is too high, and Ga-rich impurities are easily precipitated during annealing, making it difficult to obtain a single ordered face-centered cubic phase; when x is above 3.05, the DO3 phase is severely residual and cannot be completely transformed into the L12 phase, resulting in a DO3 / L12 mixed phase as the final product. The inventors have confirmed through systematic experiments that the subsequent pure phase transformation can only be achieved within this specific component range.

[0017] In step (2), the alloy ingot is made into DO3 phase strips using a single-roll melt spinning method. Single-roll melt spinning has an extremely high cooling rate (up to 10). 5 -10 6 K·s -1 Rapid solidification can effectively suppress the direct nucleation of the L12 phase during liquid-phase solidification, ensuring that the obtained precursor is a single metastable D03 phase, providing a structural basis for obtaining the pure L12 phase through solid-state phase transformation.

[0018] The annealing process in step (3) is a crucial step in the entire preparation method. The heating rate should be ≤8 K·min. -1 The purpose of annealing is to provide sufficient time for ordered atomic diffusion and lattice rearrangement, avoiding uneven phase transformation caused by excessively rapid heating. The annealing temperature of 450-550℃ is a critical window for balancing thermodynamic driving forces and kinetic feasibility: if the temperature is too low, the atomic diffusion coefficient is insufficient, limiting the kinetics of the D03→L12 phase transformation and making it difficult to complete within a reasonable time; if the temperature is too high, it may cause abnormal grain growth, surface oxidation and volatilization, and other problems, damaging the material quality. The cooling rate should be ≤8 K·min. -1 Equally crucial, rapid cooling severely inhibits L12 phase nucleation, causing the DO3 phase to be "frozen" and retained, resulting in a mixed phase rather than a pure phase as the final product. This invention effectively overcomes the technical challenge of generating a DO3 / L12 mixed phase through a combined "rapid solidification-slow desolvation" process strategy.

[0019] In a preferred embodiment of the preparation method of the present invention, the melting in step (1) is electric arc melting, which includes: placing the prepared raw materials into a vacuum electric arc furnace and evacuating the furnace to a vacuum of 1×10⁻⁶. -3 Below Pa, an arc is initiated under a protective atmosphere of 0.5-1.0 atm, and the melting is repeated 3-4 times at a melting temperature of 2000-2500℃. After cooling, the alloy ingot is obtained. The advantage of using arc melting is that it can provide a high temperature of 2000-2500℃, far exceeding the melting points of Fe and Ga, ensuring that the two metals are completely melted and thoroughly mixed. Repeated melting under a protective atmosphere 2-5 times helps to eliminate macroscopic segregation in the ingot, further improving the uniformity of the alloy composition and providing a high-quality precursor for the subsequent strip casting process.

[0020] In a preferred embodiment of the preparation method of the present invention, step (2) of single-roll melt spinning includes: placing the alloy ingot in a vacuum single-roll melt spinning device for induction remelting, and spraying it through a nozzle onto the surface of a rotating copper wheel for rapid solidification; wherein the linear velocity of the copper wheel is 10-30 m·s. -1 The cooling rate is 10 5 -10 6 K·s -1 DO3 phase alloy strips with a width of 1-5 mm and a thickness of 10-100 μm were prepared. The linear velocity of the copper wheel is the core parameter controlling the melt cooling rate: if the linear velocity is too low, cooling is insufficient, and impurity phases may appear inside the strip; if the linear velocity is too high, the strip becomes too thin and brittle, which is detrimental to subsequent annealing and device fabrication. The strip size is limited to a width of 1-5 mm and a thickness of 10-100 μm, balancing the feasibility of the strip spinning process with the annealing effect: if the thickness is too large, the temperature difference between the core and surface of the strip during annealing will be significant, affecting the uniformity of the phase transformation; if the thickness is too thin, the mechanical properties will be insufficient, and it will be prone to breakage in subsequent operations.

[0021] In a further preferred embodiment of the preparation method of the present invention, the annealing temperature in step (3) is 480-520℃, the holding time is 1-1.5 hours, and / or the heating rate is 2-5 K·min. -1 and / or a cooling rate of 2-5 K·min -1 The annealing temperature is further preferably 480-520℃, which provides sufficient driving force for atomic diffusion while avoiding grain coarsening caused by excessively high temperatures. The heating and cooling rate is preferably 2-5 K·min. -1 This makes the temperature distribution of the entire strip more uniform during the annealing process, providing ample time window for the atoms to arrange themselves in an orderly manner, thus ensuring the acquisition of high-quality, low-defect pure L12 phase crystals.

[0022] Secondly, this invention provides an ordered face-centered cubic Fe-Ga thermoelectric material prepared by the above-described method. Although the L12 phase Fe-Ga alloy itself is not an unknown phase, there is currently no effective method in the prior art to controllably prepare a pure L12 phase. The pure ordered face-centered cubic Fe-Ga thermoelectric material prepared by this invention with a specific composition range (2.85≤x≤3.05) and a specific process path (melt spinning of DO3 precursor + slow and controllable annealing) is fundamentally different from similar materials containing DO3 impurities that may exist in the prior art in terms of phase purity, microstructure quality, and the resulting transverse thermoelectric performance.

[0023] The thermoelectric material provided by the present invention exhibits a single Pm-3m space group crystal structure with a lattice constant a = 3.700 Å. The Pm-3m space group is a crystallographic representation of an ordered face-centered cubic structure (i.e., L12 phase), in which Ga atoms occupy the vertex positions of the cubic unit cell and Fe atoms occupy the face-centered positions, forming a typical A3B type ordered arrangement.

[0024] The thermoelectric material provided by the present invention has a room temperature saturation magnetization of 165-175 emu·g. -1 Preferably, the room temperature anomalous Hall resistivity of the material is 5.9-10.1 μΩ·cm.

[0025] Compared to the traditional D03 phase Fe3Ga, the L12 phase material of this invention exhibits significantly higher saturation magnetization, which stems from the enhanced magnetic exchange interaction between Fe-Fe atoms in the L12 ordered structure. Higher saturation magnetization facilitates a stronger anomalous Nernst response under zero magnetic field conditions, improving the practical performance of the device. The anomalous Hall resistivity reflects the lateral electrical transport capability related to Berry curvature in the material; the superior performance of the material in this invention in this metric is closely related to its topologically enhanced electronic structure.

[0026] In a preferred embodiment of the thermoelectric material provided by the present invention, when x = 2.95 in the chemical formula, the room temperature anomalous Nernst coefficient of the material is greater than 8.0 μV·K. -1 When x=3.05 in the chemical formula, the anomalous Nernst coefficient at room temperature of the material is negative. The component with x=2.95 corresponds to the Fermi level being located near the band with the greatest Berry curvature, causing the anomalous Nernst effect to reach its extreme value. The component with x=3.05 achieves the sign reversal of the anomalous Nernst coefficient for the first time, that is, the polarity changes. This discovery has important practical value: by utilizing the difference in polarity between different components of the same material system, a single-material thermopile can be directly constructed without splicing P-type and N-type thermoelectric arms of different materials, thus greatly simplifying the device structure and fabrication process.

[0027] Thirdly, the present invention provides a thermoelectric device comprising the aforementioned ordered face-centered cubic Fe-Ga thermoelectric material. The thermoelectric device includes, but is not limited to: a lateral thermoelectric generator, an industrial waste heat recovery device, a flexible thermal sensor, a micro energy harvester, and a single-material thermopile. Among these, the single-material thermopile is a distinctive application of the present invention, fully utilizing the Fe... x Ga 4-xThe system exhibits a large positive anomalous Nernst coefficient near x=2.95 and a negative anomalous Nernst coefficient near x=3.05. By alternating L12 phase Fe-Ga strips with different Fe contents on the same substrate, a series thermopile structure can be constructed without the introduction of dissimilar thermoelectric materials, which significantly reduces the interfacial contact resistance and thermal stress mismatch problem, while simplifying the device fabrication process and packaging process.

[0028] Compared with the prior art, the present invention can achieve one or more of the following beneficial effects:

[0029] I. First successful controllable preparation of pure L12 phase Fe-Ga alloy

[0030] This invention clarifies for the first time how to obtain pure L12 phase Fe. x Ga 4-x The alloy composition window (2.85≤x≤3.05) and annealing process parameters (temperature 450-550℃, heating and cooling rate ≤8 K·min) -1 This method effectively overcomes the problem of mixed DO3 / L12 phases caused by component deviation or improper process parameters in traditional methods. By synergistically controlling the Fe content and annealing process, a complete and controllable phase transformation from the metastable DO3 phase to the stable L12 phase is achieved, resulting in high-quality pure L12 phase materials free of DO3 and other impurities. This solves the technical problems of low phase purity and poor process repeatability in the preparation of pure L12 phases.

[0031] II. Significantly increased anomalous Nernst coefficient

[0032] The L12 phase Fe obtained by this invention x Ga 4-x The alloy exhibits significantly enhanced transverse thermoelectric properties. Specifically, the L12 phase Fe... 2.95 Ga 1.05 The room temperature anomalous Nernst coefficient is as high as 8.5 μV·K. -1 Compared to the traditional D03 phase Fe3Ga (approximately 3.6 μV·K), -1 The performance improvement is nearly doubled, setting a new record for room-temperature iron-based magnetic topological materials. This performance enhancement stems from the topological enhancement effect generated by the huge Berry curvature near the Fermi surface in the L12 ordered face-centered cubic structure, as well as the absence of impurity phase scattering in pure-phase materials, which has no adverse effects on electron transport.

[0033] III. For the first time, polarity reversal of the room-temperature anomalous Nernst effect was achieved in an iron-based binary alloy.

[0034] This invention marks the first time that the polarity of the anomalous Nernst coefficient has been controlled at room temperature in an iron-based binary alloy system. When x = 3.05, the room-temperature anomalous Nernst coefficient of the L12 phase alloy is negative (-1.3 μV·K).-1 This contrasts sharply with the positive coefficients of the iron-rich components (x=2.85-3.0). This polarity reversal characteristic allows for the construction of thermopile by utilizing the positive and negative polarity differences of different components in a single material system, eliminating the need for alternating splicing of P-type and N-type materials. This significantly simplifies the device structure and fabrication process, substantially reduces the risk of interfacial contact resistance and thermal stress mismatch, and provides a new path for the integration and miniaturization of lateral thermoelectric devices.

[0035] IV. Superior magnetic properties compared to traditional D03 phase materials, breaking through the room temperature metastable state limitation of D03 phase.

[0036] The L12 phase Fe obtained by this invention x Ga 4-x The alloy exhibits excellent magnetic properties. Its room-temperature saturation magnetization ranges from 165 to 175 emu·g. -1 It is significantly higher than the approximately 120 emu·g of traditional D03 phase Fe3Ga. -1 The significant difference between the in-plane and out-of-plane hysteresis loops of the L12 phase alloy indicates that it has high magnetocrystalline anisotropy and a higher energy barrier for domain rotation and domain wall motion. This is beneficial for obtaining a stable and efficient transverse thermoelectric response under zero magnetic field conditions, which is of great significance for the practical application of devices.

[0037] The D03 phase is metastable at room temperature, but undergoes a structural phase transition from ferromagnetic to paramagnetic to ferromagnetic L12 phase at high temperatures (around 600-700 K), severely limiting the service temperature range and operational stability of the device. The L12 phase prepared in this invention is a room-temperature stable phase with excellent crystal structure thermal stability, overcoming the performance degradation problem caused by the metastable nature of the D03 phase, and expanding the operating temperature window and applicable scenarios of iron-based lateral thermoelectric materials.

[0038] V. Overall Improvement in Electricity Transmission Performance

[0039] In addition to the anomalous Nernst coefficient, the L12 phase Fe of this invention x Ga 4-x The alloy exhibits significantly superior anomalous Hall resistivity and lateral thermoelectric conductivity compared to conventional D03 phase Fe3Ga materials. The increase in anomalous Hall resistivity reflects a significant enhancement in the lateral electrical transport capacity related to Berry curvature in the material, consistent with the topological enhancement mechanism of the anomalous Nernst effect. This verifies the intrinsic advantages of the L12 ordered face-centered cubic structure in lateral thermoelectric applications from multiple dimensions.

[0040] VI. Expanding New Application Models for Single-Material Thermopunk

[0041] Based on the feature of this invention that allows for adjustable positive and negative anomalous Nernst coefficients within the same material system, a single-material thermopile can be realized for the first time in an iron-based binary alloy. Specifically, by alternately arranging L12 phase Fe-Ga strips with positive and anomalous Nernst coefficients (e.g., x=2.95) and negative anomalous Nernst coefficients (e.g., x=3.05) on a substrate, a series structure can be formed without introducing dissimilar materials. This fundamentally avoids reliability problems such as contact resistance, thermal expansion mismatch, and interface diffusion caused by heterogeneous interfaces in traditional thermopiles, providing a new paradigm for the design of next-generation lateral thermoelectric devices. Attached Figure Description

[0042] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings, wherein:

[0043] Figure 1 The room temperature X-ray diffraction patterns of the L12 phase Fe3Ga alloy strip prepared in Example 4 of the present invention and the D03 phase Fe3Ga alloy strip prepared in Comparative Example 1 are shown.

[0044] Figure 2 The L12 phase Fe obtained in Examples 1-5 of this invention x Ga 4-x Alloy strips and Fe mixed phase DO3 / L12 prepared in Comparative Example 2 x Ga 4-x Room temperature X-ray diffraction pattern of alloy strips;

[0045] Figure 3 The magnetization intensity-temperature curves of the L12 phase Fe3Ga alloy strip prepared in Example 4 of the present invention and the D03 phase Fe3Ga alloy strip prepared in Comparative Example 1 under an applied magnetic field of 1000 Oe are shown, wherein the direction of the external magnetic field is parallel to the sample surface.

[0046] Figure 4 The magnetization-magnetic field curves of the L12 phase Fe3Ga alloy strip prepared in Example 4 of the present invention and the D03 phase Fe3Ga alloy strip prepared in Comparative Example 1 are shown at room temperature, wherein the direction of the applied magnetic field is perpendicular to the surface of the alloy strip.

[0047] Figure 5 The L12 phase Fe obtained in Examples 1-5 of this invention x Ga 4-x Alloy strips and Fe mixed phase DO3 / L12 prepared in Comparative Example 2 x Ga 4-x Magnetization intensity-temperature curves of alloy strips under an applied magnetic field of 1000 Oe, wherein the direction of the external magnetic field is parallel to the sample surface;

[0048] Figure 6 The L12 phase Fe obtained in Examples 1-5 of this invention xGa 4-x Alloy strips and Fe mixed phase DO3 / L12 prepared in Comparative Example 2 x Ga 4-x The results of the anomalous Nernst effect test of the alloy strip at room temperature, where the direction of the applied magnetic field is perpendicular to the surface of the alloy strip and the direction of the temperature gradient is parallel to the surface of the alloy strip;

[0049] Figure 7 The L12 phase Fe obtained in Examples 1-5 of this invention x Ga 4-x Alloy strips and Fe mixed phase DO3 / L12 prepared in Comparative Example 2 x Ga 4-x The results of the anomalous Hall effect test of the alloy strip at room temperature, where the direction of the applied magnetic field is perpendicular to the surface of the alloy strip. Detailed Implementation

[0050] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention.

[0051] I. The raw materials and equipment used in the examples are described below:

[0052] High-purity Fe blocks (purity ≥ 99.98 wt%) and high-purity Ga blocks (purity ≥ 99.9999 wt%) are both commercially available high-purity metal raw materials;

[0053] The equipment used for preparing alloy ingots is a WS-500 vacuum electric arc furnace; the equipment used for preparing alloy strips is a WK-I vacuum single-roll melt spinning machine; the equipment used for annealing is a high-vacuum annealing furnace;

[0054] Crystal structure characterization was performed using a Rigaku SmartLab X-ray diffractometer (XRD) equipped with a Cu Kα X-ray source;

[0055] The magnetic properties were characterized using a Quantum Design SQUID-VSM superconducting quantum interference vibrational magnetometer.

[0056] Transport performance was characterized using the Quantum Design PPMS DynaCool integrated property measurement system, equipped with a thermal transport (TTO) module.

[0057] II. L12 type Fe in the embodiments of the present invention x Ga 4-x The general preparation method of thermoelectric materials includes the following steps:

[0058] (1) According to the chemical formula Fe x Ga 4-xWeigh high-purity Fe and Ga blocks according to the stoichiometric ratio (x = 2.85, 2.95, 3.0, 3.05) for precise batching. Place the prepared raw materials into a vacuum arc furnace and evacuate to a vacuum level of 1 × 10⁻⁶. -3 Below Pa, the furnace cavity is cleaned twice with high-purity argon (purity 99.996 wt%), and then the arc is ignited under a high-purity argon protective atmosphere of 0.5-1.0 atm. The melting is repeated 3-4 times at a melting temperature of 2000-2500℃. After melting, the alloy ingot with uniform composition is obtained.

[0059] (2) The obtained alloy ingot is placed in a vacuum single-roller melting and spinning equipment, and after induction remelting, it is sprayed through a nozzle onto the surface of a rotating copper wheel for rapid solidification, wherein the linear velocity of the copper wheel is 20 m·s. -1 The cooling rate is 10 5 -10 6 K·s -1 A DO3 phase Fe with a width of approximately 2 mm and a thickness of approximately 30 μm was prepared. x Ga 4-x Alloy strips.

[0060] (3) Place the obtained D03 phase alloy strip into a high vacuum annealing furnace, evacuate to a pressure less than 5 mTorr, and anneal at 3 K·min -1 Heat to 500℃ at a heating rate of [temperature value missing], hold at that temperature, and then heat at 3 K·min [temperature value missing]. -1 The temperature was cooled to room temperature at a decreasing rate to complete the solid-state phase transformation from the DO3 phase to the L12 phase, thus obtaining pure L12 phase Fe. x Ga 4-x Thermoelectric materials.

[0061] Example

[0062] The present invention is further illustrated below through specific embodiments and comparative examples. Unless otherwise specified, the preparation steps in all embodiments and comparative examples are performed according to the aforementioned general preparation method. The components, preparation conditions, and properties of each embodiment are summarized below.

[0063] It should be noted that although Comparative Examples 1 and 2 are used as comparative examples, the materials used in their preparation are also products of the exploration process of the method of this invention or comparative samples that do not fall within the scope of protection of this invention. Strictly speaking, they can also be regarded as control experiments within the scope of this invention.

[0064] Example 1

[0065] Chemical formula Fe x Ga 4-xx=2.85, and the raw materials were prepared according to the general preparation method, including batching, electric arc melting, single-roll melt spinning, and vacuum annealing. The annealing temperature was 500℃, and the heating and cooling rates were both 3 K·min. -1 The obtained product was characterized by XRD as pure L12 phase Fe. 2.85 Ga 1.15 The alloy strip, after testing, has an anomalous Nernst coefficient of 6.1 μV·K at room temperature. -1 .

[0066] Example 2

[0067] Chemical formula Fe x Ga 4-x x=2.9, and the raw materials were prepared according to the general preparation method, including batching, electric arc melting, single-roll melt spinning, and vacuum annealing. The annealing temperature was 500℃, and the heating and cooling rates were both 3.5 K·min. -1 The obtained product was characterized by XRD as pure L12 phase Fe. 2.9 Ga 1.1 The alloy strip, after testing, has an anomalous Nernst coefficient of 6.3 μV·K at room temperature. -1 .

[0068] Example 3

[0069] Chemical formula Fe x Ga 4-x x=2.95, and the raw materials were prepared according to the general preparation method, including batching, electric arc melting, single-roll melt spinning and vacuum annealing, with an annealing temperature of 500℃ and a heating and cooling rate of 3 K·min. -1 The obtained product was characterized by XRD as pure L12 phase Fe. 2.95 Ga 1.05 The alloy strip, after testing, has an anomalous Nernst coefficient of 8.5 μV·K at room temperature. -1 .

[0070] Example 4

[0071] Chemical formula Fe x Ga 4-x x=3.0, and the materials were prepared according to the general method, including batching, electric arc melting, single-roll melt spinning, and vacuum annealing, with an annealing temperature of 500℃ and a heating and cooling rate of 3 K·min. -1 The obtained product was characterized by XRD as pure L12 phase Fe3Ga alloy strips, and its room temperature anomalous Nernst coefficient was measured to be 6.6 μV·K. -1 .

[0072] Example 5

[0073] Chemical formula Fex Ga 4-x x=3.05, and the raw materials were prepared according to the general preparation method, including batching, electric arc melting, single-roll melt spinning and vacuum annealing, with an annealing temperature of 500℃ and a heating and cooling rate of 3 K·min. -1 The obtained product was characterized by XRD as pure L12 phase Fe. 3.05 Ga 0.95 The alloy strip, after testing, has an anomalous Nernst coefficient of -1.3 μV·K at room temperature. -1 This achieves a polarity reversal of the anomalous Nernst effect.

[0074] Comparative Example 1

[0075] Chemical formula Fe x Ga 4-x The sample, with x=3.0, was prepared using a standard method involving batching, arc melting, and single-roll melt spinning, but without vacuum annealing to retain the original DO3 phase. XRD characterization revealed the product to be a pure DO3 phase Fe3Ga alloy ribbon, with a room-temperature anomalous Nernst coefficient of 3.6 μV·K. -1 .

[0076] Comparative Example 2

[0077] Chemical formula Fe x Ga 4-x x=3.09, and the raw materials were prepared according to the general preparation method, including batching, electric arc melting, single-roll melt spinning, and vacuum annealing. The annealing temperature was 500℃, and the heating and cooling rates were both 3 K·min. -1 The obtained product was characterized by XRD as a DO3 / L12 mixed phase Fe. 3.09 Ga 0.91 The alloy strip, after testing, has an anomalous Nernst coefficient of 4.3 μV·K at room temperature. -1 No polarity reversal of the anomalous Nernst effect was observed.

[0078] Performance testing, characterization and analysis

[0079] 1. Crystal structure characterization

[0080] The L12 phase Fe3Ga alloy strips prepared in Example 4 and the D03 phase Fe3Ga alloy strips prepared in Comparative Example 1 were analyzed by room temperature X-ray diffraction using a Cu Kα X-ray diffractometer. The results are as follows: Figure 1As shown. The XRD pattern of the unannealed sample in Comparative Example 1 only shows the characteristic diffraction peaks of the D03 phase, corresponding to the (220), (400), and (422) crystal planes, with a lattice constant of a = 5.812 Å. In the XRD pattern of the sample in Example 4, only the characteristic diffraction peaks of the L12 phase appear, corresponding to the (111), (200), (220), and (311) crystal planes, respectively. A dedicated (110) diffraction peak of the L12 phase is observed at 2θ = 34.22°. No diffraction peaks of the D03 phase or other impurity phases are detected, proving that the prepared material is a completely pure L12 structure with a lattice constant of a = 3.700 Å.

[0081] Fe with different compositions and crystal phases x Ga 4-x The alloy strips were subjected to room temperature XRD comparative analysis, and the results are as follows: Figure 2 As shown. The alloy samples with x=2.85-3.05 prepared in Examples 1-5 all exhibited only L12 phase characteristic diffraction peaks in their XRD patterns, indicating that they were all completely pure L12 phase structures. The XRD pattern of Comparative Example 2 (x=3.09) showed both L12 phase (110) diffraction peaks and DO3 phase (220) diffraction peaks, exhibiting a typical two-phase mixed structure. These results demonstrate that, only within the composition range of 2.85≤x≤3.05, combined with the annealing process of this invention, pure L12 phase Fe can be obtained. x Ga 4-x Alloy; if the composition exceeds this range, a pure phase cannot be obtained, and the product is a DO3 / L12 mixed phase.

[0082] 2. Characterization of Magnetic Properties

[0083] The magnetization-temperature (MT) curves of the L12 phase Fe3Ga alloy strips prepared in Example 4 and the D03 phase Fe3Ga alloy strips prepared in Comparative Example 1 were measured using a superconducting quantum interference vibrational sample magnetometer (SQUID-VSM). An external magnetic field of 1000 Oe was applied. The results are as follows: Figure 3 As shown in the MT curve, the magnetization of the D03 phase Fe3Ga alloy in Comparative Example 1 decreases sharply in the temperature range of 600-700 K, and then increases sharply in the temperature range of 700-750 K, eventually approaching the saturation magnetization value of the L12 phase Fe3Ga in Example 4. This phenomenon indicates that the D03 phase underwent a structural phase transformation process from ferromagnetic to paramagnetic to L12 phase ferromagnetic state, which is in perfect agreement with the XRD results.

[0084] Comparison of room temperature magnetization-magnetic field (MH) curves, for example Figure 4 As shown. The saturation magnetization of the L12 phase Fe3Ga alloy prepared in Example 4 is approximately 170 emu·g. -1It is significantly higher than the saturation magnetization of the D03 phase Fe3Ga alloy prepared in Comparative Example 1 (approximately 120 emu·g). -1 Furthermore, the significant difference between the in-plane and out-of-plane hysteresis loops of the L12 phase alloy indicates that its magnetocrystalline anisotropy is far superior to that of the D03 phase, and its energy barrier for domain rotation and domain wall motion is higher, which is more conducive to device applications under zero magnetic field.

[0085] The alloy strips of Examples 1 to 5 and Comparative Example 2 were further subjected to MT curve testing under an external magnetic field of 1000 Oe, and the results are as follows. Figure 5 As shown, samples from Examples 1 to 5 all exhibited structural phase transition characteristics from the D03 phase to the L12 phase, while Comparative Example 2 (x=3.09) did not show a significant structural phase transition. This result is consistent with... Figure 2 The XRD patterns shown are completely consistent.

[0086] 3. Transport performance characterization

[0087] The thermal transport module (TTO) of the integrated physical property measurement system (PPMS) was used to analyze the obtained L12 phase Fe. x Ga 4-x The room temperature anomalous Nernst effect and anomalous Hall effect of the alloy strip were tested and characterized.

[0088] (1) Anomalous Nernst effect

[0089] The results of the anomalous Nernst effect test are as follows: Figure 6 As shown. At room temperature, the anomalous Nernst coefficient of Example 3 (x=2.95) reaches 8.5 μV·K. -1 This is the highest value currently achieved for room-temperature iron-based magnetic topological materials. The room-temperature anomalous Nernst coefficient of Example 5 (x=3.05) is -1.3 μV·K. -1 Anomalous Nernst polarity reversal was achieved at room temperature. The room-temperature anomalous Nernst coefficient of Example 4 (L12 phase Fe3Ga) was 6.6 μV·K. -1 Compared with the D03 phase sample of Comparative Example 1 (3.6 μV·K), -1 The anomalous Nernst coefficient values ​​of Examples 1 and 2 are nearly twice that of Examples 2, at 6.1 μV·K. -1 and 6.3 μV·K -1 Slightly lower than Example 4.

[0090] (2) Anomalous Hall effect

[0091] The results of the anomalous Hall effect test are as follows: Figure 7As shown. At room temperature, the anomalous Hall resistivity values ​​of Example 2 (x=2.9) and Example 3 (x=2.95) are similar, approximately 10.1 μΩ·cm. The anomalous Hall resistivity values ​​of Example 1 (x=2.85), Example 4 (x=3.0), and Example 5 (x=3.05) are 7.9 μΩ·cm, 6.5 μΩ·cm, and 5.9 μΩ·cm, respectively.

[0092] 4. Based on the above test and characterization results, the following conclusions can be drawn:

[0093] First, to ensure the acquisition of pure L12 phase Fe x Ga 4-x To achieve optimal transverse thermoelectric performance in thermoelectric materials, the Fe composition must be strictly controlled within the range of 2.85 ≤ x ≤ 3.05, and the material must be heated using a vacuum degree of less than 5 mTorr, an annealing temperature of 500℃, and a heating / cooling rate of 3 K·min. -1 Annealing process.

[0094] Second, L12 phase Fe x Ga 4-x The anomalous Nernst effect, magnetic properties, and electrical transport properties of the alloy are all superior to those of the metastable D03 phase Fe-Ga alloy. Among them, the L12 phase Fe... 2.95 Ga 1.05 (x=2.95) maximized the anomalous Nernst coefficient at room temperature (8.5 μV·K). -1 L12 phase Fe 3.05 Ga 0.95 (x=3.05) For the first time at room temperature, the polarity reversal of the anomalous Nernst coefficient (-1.3 μV·K) was achieved. -1 ).

[0095] L12 phase Fe prepared by this invention x Ga 4-x Thermoelectric materials possess advantages such as the giant anomalous Nernst effect, room temperature polarity tunability, controllable pure-phase preparation, and stable processing. They effectively solve the technical problems of low performance and inability to achieve polarity control in traditional iron-based thermoelectric materials, and have significant application prospects in fields such as lateral thermoelectric power generation, industrial waste heat recovery, flexible thermal sensing, and micro energy harvesting.

Claims

1. A method for preparing an ordered face-centered cubic Fe-Ga thermoelectric material, characterized in that, Includes the following steps: (1) According to the chemical formula Fe x Ga 4-x The ingredients are batched and smelted to obtain an alloy ingot, where 2.85 ≤ x ≤ 3.05; (2) The alloy ingot is processed into DO3 phase alloy strips by single-roll melt spinning; (3) The D03 phase alloy strip is annealed under vacuum conditions, the annealing process including: first at ≤8K·min -1 Heat to an annealing temperature of 450-550℃ at a heating rate, hold at that temperature, and then heat at ≤8 K·min. -1 The temperature is cooled to room temperature at a cooling rate that transforms the D03 phase into the pure L12 phase, thus obtaining the ordered face-centered cubic Fe-Ga thermoelectric material.

2. The preparation method according to claim 1, wherein, In step (1), the melting is electric arc melting, which includes: placing the prepared raw materials into a vacuum electric arc furnace and evacuating the furnace to a vacuum level of 1×10⁻⁶. -3 The alloy ingot is obtained by igniting an arc under a protective atmosphere of 0.5-1.0 atm below Pa, repeatedly melting 2-5 times at a melting temperature of 2000-2500℃, and then cooling.

3. The preparation method according to claim 1, wherein, In step (2), the single-roll melt spinning includes: placing the alloy ingot in a vacuum single-roll melt spinning device for induction remelting, and spraying it through a nozzle onto the surface of a rotating copper wheel for rapid solidification; wherein the linear velocity of the copper wheel is 10-30 m·s. -1 The cooling rate is 10 5 -10 6 K·s -1 DO3 phase alloy strips with a width of 1-5 mm and a thickness of 10-100 μm were prepared.

4. The preparation method according to claim 1, wherein, In step (3), the annealing temperature is 480-520℃, the holding time is 1-1.5 hours, and / or the heating rate is 2-5 K·min. -1 And / or the cooling rate is 2-5 K·min -1 .

5. An ordered face-centered cubic Fe-Ga thermoelectric material, characterized in that, It is prepared by any one of claims 1 to 4.

6. The thermoelectric material according to claim 5, wherein, The material exhibits a single Pm-3m space group crystal structure with a lattice constant a = 3.700 Å.

7. The thermoelectric material according to claim 5, wherein, The room temperature saturation magnetization of the material is 165-175 emu·g. -1 ; and / or the room temperature anomalous Hall resistivity of the material is 5.9-10.1 μΩ·cm.

8. The thermoelectric material according to claim 5, wherein, In the chemical formula of the material, x = 2.95, and the anomalous Nernst coefficient at room temperature is greater than 8.0 μV·K. -1 ; and / or In the chemical formula of the material, x = 3.05, and the room temperature anomalous Nernst coefficient of the material is negative.

9. A thermoelectric device, characterized in that, The thermoelectric material comprising any one of claims 5 to 8, an ordered face-centered cubic Fe-Ga material.

10. The thermoelectric device according to claim 9, wherein, The thermoelectric devices include: lateral thermoelectric generators, industrial waste heat recovery devices, flexible thermal sensors, micro energy harvesters, and single-material thermopile.